2004
DOI: 10.1081/cnv-200039658
|View full text |Cite
|
Sign up to set email alerts
|

CD44s Expression in Resectable Colorectal Carcinomas and Surrounding Mucosa

Abstract: CD44s may play a role in the tumorogenesis of colorectal carcinomas. In addition, CD44s levels in tumor-surrounding mucosa may provide, in concert with some clinicopathological parameters, important information about prognostic evaluation of patients with resectable colorectal carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
2
21
2
Order By: Relevance
“…Ylagan et al and Asao et al reported that the loss of CD44s expression reflects tumor aggressiveness [6,7], while Fernandez et al found a significant relationship between CD44s expression and a high proliferation rate and aggressiveness in CRC [3]. Huh et al and Ropponen et al also observed that high-grade and high-stage CRC overexpressed the CD44s and that this was associated with lower cancer-related survival [1,4] Our study was undergone to estimate the CD44s expression of the tumor cells at the deepest invaded area because there has been a report that CD44s expression in the invaded area is a sensitive marker for lymph node metastasis [7].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ylagan et al and Asao et al reported that the loss of CD44s expression reflects tumor aggressiveness [6,7], while Fernandez et al found a significant relationship between CD44s expression and a high proliferation rate and aggressiveness in CRC [3]. Huh et al and Ropponen et al also observed that high-grade and high-stage CRC overexpressed the CD44s and that this was associated with lower cancer-related survival [1,4] Our study was undergone to estimate the CD44s expression of the tumor cells at the deepest invaded area because there has been a report that CD44s expression in the invaded area is a sensitive marker for lymph node metastasis [7].…”
Section: Discussionmentioning
confidence: 97%
“…Reduced CD44s expression has been shown to be associated with a high incidence of lymph-vascular permeation in endometrial carcinoma [12] and breast carcinoma [8] and poor prognosis in patients with pancreatic carcinoma, thyroid carcinoma, and squamous cell carcinoma of the head and neck [13,14]. Similarly, the clinical significance of the CD44s in the progression and metastasis of CRC is also controversial [1][2][3][4][5][6][7]. Various studies may have been controversial because of different antibodies, differences in immunohistochemistry methods, patient material, and duration of follow-up [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have provided evidence of decreased survival in CRC patients overexpressing CD44 and COX-2 [4][5][6][7][8][14][15][16]. However, relatively few studies have compared the prognostic value of CD44 and COX-2 expression in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several CD44 isoforms (standard and variant) occur as a result of alternative splicing, thereby providing significant heterogeneity in CD44 expression among different tissues; however, contradictory results have been reported regarding their clinical significances in the progression and metastasis of CRC [5,15,[26][27][28][29]. In this study, we evaluated mRNA expression for the CD44 standard isoform only.…”
Section: Discussionmentioning
confidence: 99%